2012
DOI: 10.1007/978-94-007-4765-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Assembly of G Protein βγ Dimers: Comparison of In Vitro and In Vivo Studies

Abstract: The heterotrimeric GTP-binding proteins (G proteins) are the canonical cellular machinery used with the approximately 700 G protein-coupled receptors (GPCRs) in the human genome to transduce extracellular signals across the plasma membrane. The synthesis of the constituent G protein subunits, and their assembly into Gβγ dimers and G protein heterotrimers, determines the signaling repertoire for G-protein/GPCR signaling in cells. These synthesis/assembly -processes are intimately related to two other overlappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 121 publications
(213 reference statements)
1
20
0
Order By: Relevance
“…With the exception of the β 5 -subunit, all combinations of the other four β-subunits (β 1 -β 4 ) and 12 γ-subunits (γ 1 -γ 5 and γ 7 -γ 13 ) were found to interact with the two different α-subunits. This finding was unexpected because other investigators had indicated that certain βγ-dimers (e.g., β 2 γ 1 , β 2 γ 11 , β 2 γ 13 , β 3 γ 1 , and β 3 γ 11 ) do not exist (6,(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…With the exception of the β 5 -subunit, all combinations of the other four β-subunits (β 1 -β 4 ) and 12 γ-subunits (γ 1 -γ 5 and γ 7 -γ 13 ) were found to interact with the two different α-subunits. This finding was unexpected because other investigators had indicated that certain βγ-dimers (e.g., β 2 γ 1 , β 2 γ 11 , β 2 γ 13 , β 3 γ 1 , and β 3 γ 11 ) do not exist (6,(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, those combinations-especially for β 3 and β 5 -that cannot be generated by in vitro translation could still be found in cell-based assays like the yeast two-hybrid screen (29), coimmunoprecipitation (31), and bimolecular fluorescence complementation (47), as summarized in detail in ref. 6. Similarly, the β 2 γ 13 -dimer, which could not be identified when mixing subunits that had been separately translated in vitro (32), could be identified when both subunits were cotranslated in vitro (37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1D). Newly synthetized G-protein β-subunit polypeptides assume their final shape inside the cytosolic chaperonin containing T-complex protein 1 (CCT), whereas Gγ subunits (aided by the phosducin-like protein, PhLP) (13) play a critical role in stabilizing and releasing Gβ from CCT to yield mature Gβγ complexes (14)(15)(16)(17). Therefore, the lack of Gγ 1 in rods may result in Gβ 1 retention inside CCT, ultimately reducing the CCT availability to process the dozens of other cytosolic proteins normally folded inside this chaperonin (18).…”
Section: Resultsmentioning
confidence: 99%